Menafsir Ulang Hijab: Dinamika dan Makna Dalam Konteks Global : Konsumen Griya Busana Muslim Indramayu - Fitriana Maghdalena; Zulkiply Lessy (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This article discusses the dynamics of wearing jilbab and its meaning in the context of globalization, focusing on the influence of cultural globalization on norms, values, and lifestyles in religious traditions. This research is a qualitative study using a netnography approach with data obtained from the response of the Indramayu Muslim fashion griya whatsApp group. This article discusses the evolution of the concept of hijab from a separator between free women and slaves to a tool to protect women's private parts from prying eyes. In addition, the article also highlights the different views on hijab, including the views of contemporary scholars and the impact of globalization on the views and practices of hijab in contemporary society. Thus, this article highlights how globalization, fashion trends, religious identity, and cultural values affect the dynamics of hijab and its meaning in contemporary society.